2008
DOI: 10.1108/02621710810840794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of learning goals on emotional, social, and cognitive intelligence competency development

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Thus, an improved LoC‐I may help cultivate a mastery of academic content (Kirkpatrick, Stant, Downes, & Gaither, ). These findings reflect a positive psychological impact of the MBA educational program, consistent with the previously reported research showing improvements in EI (Boyatzis, ) and interpersonal skills (Kretovics, ; Leonard, ). The psychology program is focused on theory and research competency rather than interpersonal competencies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, an improved LoC‐I may help cultivate a mastery of academic content (Kirkpatrick, Stant, Downes, & Gaither, ). These findings reflect a positive psychological impact of the MBA educational program, consistent with the previously reported research showing improvements in EI (Boyatzis, ) and interpersonal skills (Kretovics, ; Leonard, ). The psychology program is focused on theory and research competency rather than interpersonal competencies.…”
Section: Discussionsupporting
confidence: 91%
“…However, this latter study involved different groups of entering and exiting MBA students who were combined and assessed at the same time, rather than longitudinal gain scores. A longitudinal study using the same measure found significant improvements in helping, leadership and relationship skills (Leonard, 2008 to explore whether these psychological competencies influence academic achievement.…”
Section: Ei Se Loc and The Mbamentioning
confidence: 99%
“…20–21): A course on Leadership Assessment and Development (LEAD) using Intentional Change Theory (ICT) as the basis for design (Boyatzis & Saatcioglu, ; Goleman, Boyatzis, & McKee, ). Course design focused on developing the “whole person” and also four benchmarks, including completion of (a) a personal vision, (b) a personal balance sheet (identifying personal strengths, areas for improvement), (c) coaching sessions with a leadership coach, and (d) a learning agenda (creating a personal plan for leadership development; Boyatzis et al., ; Leonard, ). An explicit shift to a philosophy of experiential learning and applied pedagogy (Kolb, ; Kolb & Kolb, ; Lingham, ). A focus on specific competencies in selected courses while addressing course materials (e.g., a marketing course that assessed students on their presentation skills). Required participation in field projects (i.e., group work and peer collaboration on projects in real life companies, organizations, and workplaces). Opportunities to participate in voluntary activities such as marketing clubs. …”
Section: Developing the Whole Person To Be Effectivementioning
confidence: 99%
“…Intentional Change Theory (ICT) as the basis for design (Boyatzis & Saatcioglu, 2008;Goleman, Boyatzis, & McKee, 2002). Course design focused on developing the "whole person" and also four benchmarks, including completion of (a) a personal vision, (b) a personal balance sheet (identifying personal strengths, areas for improvement), (c) coaching sessions with a leadership coach, and (d) a learning agenda (creating a personal plan for leadership development; Boyatzis et al, 2010;Leonard, 2007). 2.…”
Section: A Course On Leadership Assessment and Development (Lead) Usingmentioning
confidence: 99%
“…A partir de um estudo empírico, Leonard (2008) revela que o estabelecimento de metas de aprendizagem é particularmente importante para o desenvolvimento de competências, pois estas foram mais desenvolvidas em indivíduos que fixaram esses objetivos. Para chegar nessa conclusão, o autor fez um estudo que variou de nove meses a quatro anos e meio, com alunos de um programa de MBA.…”
Section: Rmcunclassified